Delayed cord clamping: Perceptions, practices and influencers among the healthcare providers of selected healthcare facilities in Bangladesh. - Sabrina Jabeen; Shumona Sharmin Salam; Siobhan Gillespie; Mehedi Hasan; Sharmin Islam; Anika Tasneem Chowdhury; Shafiqul Ameen; Julie Balen; Ahmed Ehsanur Rahman; Shams El Arifeen; Quamrun Nahar; Dilly Oc Anumba (PLoS ONE)
Background Umbilical cord clamping is a procedure of separating the newborn after birth with varying recommendations worldwide based on the timing of clamping. Although the benefits of delayed cord clamping (DCC) have been acknowledged, there is a lack of understanding regarding healthcare providers' perceptions and practices, particularly in Bangladesh. This study aimed to explore the perceptions, practices, and influencers of DCC among healthcare providers in selected secondary-level healthcare facilities in Bangladesh. Methods This qualitative study was conducted at two public healthcare facilities. Purposive sampling was used to select 30 participants for in-depth and key-informant interviews and non-participatory observations for 13 deliveries were done. A thematic analysis approach was employed to identify emerging themes, and interpretive phenomenological analysis of the observations helped verify and contextualise the reported practices. Statistical software N-Vivo (Version-12, Denver) was used for data analysis. Results Healthcare providers perceived that cord clamping should occur after one to three minutes, primarily informed by international literature, maternal health training, or peer guidance. Providers recognised DCC's benefits, such as enhanced bonding and reduced neonatal blood transfusions, and noted potential risks of early cord clamping like delayed adaptation and hypoxia. Observation of clamping practices revealed that most providers clamped after pulsation stopped or within three minutes, while caesarean sections often required immediate clamping. Variations existed in the number and type of clamps, with an absence of standardised guidelines. Influencing factors include the cultural impact of Traditional Birth Attendants (Dais), lack of formal training, clinical emergencies, and service delivery challenges such as high patient volumes and staff shortages. Peer learning was a major influencer of practices. Conclusion Despite having a perception regarding DCC, gaps were identified in the practice of healthcare providers. Addressing this gap and the identified influencers will require the involvement of healthcare workers, guidance developers and planners across policy and practice.